2015
DOI: 10.1097/mlr.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Patient and Nurse Outcomes Associated With Magnet Hospital Recognition

Abstract: Background Research has documented an association between Magnet hospitals and better outcomes for nurses and patients. However, little longitudinal evidence exists to support a causal link between Magnet recognition and outcomes. Objective To compare changes over time in surgical patient outcomes, nurse-reported quality, and nurse outcomes in a sample of hospitals that attained Magnet recognition between 1999 and 2007 with hospitals that remained non-Magnet. Research Design Retrospective, two-stage panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(203 citation statements)
references
References 34 publications
8
177
0
18
Order By: Relevance
“…Regional studies showed similar results. 11 These analyses confirmed the findings of Aiken et al 30 in their original study based on the 1983 cohort of Magnet hospitals. Petit Dit Dariel and Regnaux 31 in a recent meta-analysis identified significant methodological drawbacks in all these studies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Regional studies showed similar results. 11 These analyses confirmed the findings of Aiken et al 30 in their original study based on the 1983 cohort of Magnet hospitals. Petit Dit Dariel and Regnaux 31 in a recent meta-analysis identified significant methodological drawbacks in all these studies.…”
Section: Discussionsupporting
confidence: 80%
“…Some have shown improved outcomes in Magnet hospitals for elderly Medicare medical and surgical patients. 10,11 However, other investigators did not demonstrate such benefit. [12][13][14] The main limitation of these and other retrospective analyses is the lack of control for unmeasured confounding, stemming from the nonrandom patient allocation to particular hospitals.…”
Section: T He American Nurses Credentialingmentioning
confidence: 90%
“…Garantir um ambiente de prática favorável é uma das formas de melhorar a segurança e a qualidade do cuidado. 5,13 Na avaliação do ambiente da prática, os profissionais da equipe de enfermagem avaliaram como positivo o ambiente da prática profissional, com destaque para a questão da autonomia. Dessa forma, o estudo revela que a equipe de enfermagem considera ter liberdade para tomar decisões sobre o cuidado do paciente e possui responsabilidade pelo seu trabalho, o que tem sido identificado como componente importante na satisfação profissional.…”
Section: Discussionunclassified
“…Esses resultados foram replicados e hoje a designação Magnet® Hospitals certifica a instituição de saúde como bons locais para os enfermeiros trabalharem. 4,5 O burnout é uma síndrome caracterizada por exaustão emocional, despersonalização e diminuição da realização pessoal, em resposta às fontes crônicas de estresse, e tem sido identificado como um fenômeno comum entre os enfermeiros de todo o mundo. 6,7 Muitos estudos têm comprovado que as relações entre o ambiente de trabalho favorável e baixos níveis de burnout na equipe de enfermagem geram impactos positivos como melhor qualidade do cuidado oferecido, alta satisfação do profissional com o seu trabalho, baixo turnover e pouca intenção de deixar o trabalho e a profissão.…”
Section: Introductionunclassified
“…Current research confirms that when teams work collaboratively and interdependently, patient outcomes are enhanced [18][19][20][21]. Future research could elaborate the reference point established by our qualitative findings and pursue empirical knowledge about holistic and responsive workforce development such as measurement of the strength of team membership and its association with indicators of individual, patient and organizational outcomes.…”
Section: Strengths Limitations and Future Researchmentioning
confidence: 95%